Fluorine as a Hydrogen‐Bond Acceptor: Experimental Evidence and Computational Calculations. Issue 35 (17th July 2014) - Dalvit, Claudio; Invernizzi, Christian; Vulpetti, Anna
Abstract Hydrogen‐bonding interactions play an important role in many chemical and biological systems. Fluorine acting as a hydrogen‐bond acceptor in intermolecular and intramolecular interactions has been the subject of many controversial discussions and there are different opinions about it. Recently, we have proposed a correlation between the propensity of fluorine to be involved in hydrogen bonds and its 19F NMR chemical shift. We now provide additional experimental and computational evidence for this correlation. The strength of hydrogen‐bond complexes involving the fluorine moieties CH2F, CHF2, and CF3 was measured and characterized in simple systems by using established and novel NMR methods and compared to the known hydrogen‐bond complex formed between acetophenone and p‐fluorophenol. Implications of these results for 19F NMR screening are analyzed in detail. Computed values of the molecular electrostatic potential at the different fluorine atoms and the analysis of the electron density topology at bond critical points correlate well with the NMR results.